2018
DOI: 10.1007/s41104-018-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

Biogenous ethers: production and operation in a diesel engine

Abstract: Fuels from lignocellulosic biomass have the potential to contribute to sustainable future mobility targets by reducing the fossil CO 2 emissions of the transport sector. Of special interest for the diesel engine are oxygenated fuels, since they can help to solve traditional conflicts of objectives like the soot-NOx trade-off or the efficiency-NOx compromise. Dibutyl ether (DBE) and oxymethylene ethers (OME) are among the most promising fuel candidates. The suitability of these compounds for diesel engines is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 24 publications
3
20
0
1
Order By: Relevance
“…The authors also emphasized that NO x emissions are mostly dominated by the exhaust gas recirculation (EGR) rate, while fuel properties become more relevant at low EGR rates. Nevertheless, several studies showed higher raw NO x emissions from DMM-/OME n -diesel blend combustion regardless of the level of the blending rate [52,53,56]. The reasons for this are the longer phases of higher temperatures and locally increased λ values with OME n combustion, higher flame temperatures, and the lower LHV of OME n (blends), leading to a higher oxygen concentration in the exhaust gas compared to diesel fuel.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors also emphasized that NO x emissions are mostly dominated by the exhaust gas recirculation (EGR) rate, while fuel properties become more relevant at low EGR rates. Nevertheless, several studies showed higher raw NO x emissions from DMM-/OME n -diesel blend combustion regardless of the level of the blending rate [52,53,56]. The reasons for this are the longer phases of higher temperatures and locally increased λ values with OME n combustion, higher flame temperatures, and the lower LHV of OME n (blends), leading to a higher oxygen concentration in the exhaust gas compared to diesel fuel.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed significant soot and therefore PM emission reduction for small DMM/OMEn blending rates at low load points. However, when loads are increased, PM reductions decrease or become zero [56,57]. Furthermore, Oxygenated fuels reveal a high particulate emission reduction potential through the oxygen content in the fuel molecular structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Production of hydrogen by water electrolysis employing electricity from wind power is a key step of this procedure. In a very recent study, production of different oxygenate fuels (fatty acid methyl ester, dibutyl ether and OMEs) has been evaluated and the advantages of OMEs have been outlined .…”
Section: Evaluation Of Ome Fuelsmentioning
confidence: 99%